A social similarity-aware multicast routing protocol in delay tolerant networks. (1st January 2013) - Deng, Xia; Wang, Jianxin; Liu, Yao; Chang, Le
In delay tolerant networks (DTNs), multicast is widely adopted for emergency notifications in crisis environment and data scattering under military rescue situations, as it has better robustness and resource utilisation. Although the topology of DTNs usually changes quickly, they also demonstrate relatively stable social characteristics, e.g., the social similarity. In this paper, a social similarity-aware multicast routing protocol (SSM) is proposed, in which the social similarity is quantified as the probability of the encounter of two nodes in the future based on the number of common neighbours in the history. We propose and evaluate four measuring metrics (i.e., max, min, average and median) on such probability in multicast scenarios, and nodes with higher such similarity metrics are selected in priority to construct the forwarding group during the data replication process. Simulation results show that SSM can effectively improve the data delivery ratio and reduce the overhead at the same time.